(untitled) (Proceedings of the Global Public Health Conference, 2022)
Suicide is increasingly becoming a public health concern. Reporting and portrayal of suicide in media may largely contribute to this. Gaining an insight into the pattern and possible risk factors may help in the design of effective preventive measures. The aim of the study was to generate a 2-year data of suicide reportage in media in Nigeria. This was a retrospective purposive Content analysis of all media suicide reportage in Nigeria between January 2019 - December 2020. Data was entered into an excel spread sheet. Duplication was avoided. The statistical package for social sciences, version 22 was used for analysis. Frequencies and percentages of relevant variables were generated. Chi square and Fisher’s exact test was used to assess associations. Significant value was set at p<0.05. One hundred and eighteen suicide deaths were identified. Mean age was 30.65+ 12.66 with highest rate among age 20-39 years (51.7%). Majority were males (73.7%). Commonest method used was pesticide ingestion (56.8%) followed by hanging (27.1%). Identifiable associated factors included financial challenges, academic challenges, and relational problems. Pesticide use was commoner among younger age group (p< 0.001) and female sex (p < 0.024). The common use of organophosphates which is used in pesticides may be due to the fact that it is a common household tool used to control insects and rodents in many low- and middle-income countries. It is easy to access and affordable, these coupled with social media reportage makes it a ready tool especially for those already contemplating suicide. The study highlights the current reality of suicides in Nigeria. It brings to the fore, the need for proper surveillance to drive a contextualized approach to suicide prevention.